Constructional Value and Prototypicality of Metonymies for Advising. Against a Strong Reading of the Foundational Thesis of Pragmalinguistics [Valor Construccional y Prototipicidad de Metonimias Para Aconsejar. Contra Una Lectura Fuerte de la Tesis Fundacional de la Pragmática Lingüística] - Quezada-Pulido, W (Pontificia Universidad Catolica de Chile, 2018)
In this paper we analyze the data collected in an exploratory test, designed to establish a measure of the advise illocutionary force of the 15 utterances. The analysis shows that the pragmatic reading of expressions depends largely on their constructional features, as Pérez (2001), Ruiz de Mendoza & Baicchi (2007) and Del Campo (2012, 2013) have proposed within the framework of the study on illocutionary constructions. Consequently, it is not valid to state a strong interpretation of Wittgenstein s (1953) thesis that "the meaning is the use in the language". This interpretation, rejected, among others, by Searle (1969), imposes an insurmountable limitation to the explanatory pretensions of pragmalinguistics, which does not correlate with our results. © 2018 Pontificia Universidad Catolica de Chile. All rights reserved.